1992
DOI: 10.1021/bi00140a010
|View full text |Cite
|
Sign up to set email alerts
|

A kinetic and allosteric model for the acetylcholine transporter-vesamicol receptor in synaptic vesicles

Abstract: The ligand binding relationship between the acetylcholine transporter (AcChT) and the vesamicol receptor (VR) and the kinetics of active transport were studied in synaptic vesicles purified from the Torpedo electric organ using analogues of AcCh and vesamicol. Methoxyvesamicol, which should exhibit better equilibration properties for kinetics measurements than the more potent parent, inhibits active transport in a nonlinear noncompetitive manner. AcCh analogues competitively inhibit binding of [3H]vesamicol wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
50
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 24 publications
5
50
0
Order By: Relevance
“…In ex vivo studies, [ 123 I]-IBVM binds with high affinity (subnanomolar range) and high selectivity to the vesicular ACh transporter (VAChT), with a good specific-to-nonspecific ratio and with a binding in ACh-rich brain areas that is both saturable and specific (Altar and Marien, 1988;Bahr et al, 1992;Zea-Ponce et al, 2005).…”
Section: C]-pmp [mentioning
confidence: 99%
“…In ex vivo studies, [ 123 I]-IBVM binds with high affinity (subnanomolar range) and high selectivity to the vesicular ACh transporter (VAChT), with a good specific-to-nonspecific ratio and with a binding in ACh-rich brain areas that is both saturable and specific (Altar and Marien, 1988;Bahr et al, 1992;Zea-Ponce et al, 2005).…”
Section: C]-pmp [mentioning
confidence: 99%
“…Vesicular acetylcholine transporter (VAChT) 1 translocates acetylcholine (ACh) from cytoplasm to the lumen of synaptic vesicles for evoked release from nerve terminals. Vesicular protons provided by V-ATPase are used by VAChT to power ACh transport.…”
mentioning
confidence: 99%
“…When external ACh binds to outwardly oriented transporter, vesamicol cannot bind (1). External ACh presumably cannot bind to inwardly oriented transporter because the ACh-binding site is not exposed.…”
mentioning
confidence: 99%
“…In this process, it is suggested that the loss of a proton leads to a conformational change which makes the transporter active (2). Vesamicol ((-)-trans-2-(4-phenylpiperidino)cyclohexanol) has been shown to be a specific inhibitor of ACh transport by VAChT (3,4). This compound acts in a noncompetitive manner; however ACh blocks vesamicol binding to the transporter.…”
mentioning
confidence: 99%